Upaya Guru BK dalam Membantu Penyesuaian Diri Peserta Didik Berkebutuhan Khusus di SMK N 4 Padang - Trisnawati, Trisnawati; Ibrahim, Indra; Zaini, Ahmad (Bimbingan dan Konseling, 2014)
The research is done based phenomenon which is happened in the field where special necessity of participant with normal participant gather knowledge in education world so that special necessity of participant is difficult to adapt oneself in life. The purpose of this research is to describe: 1) The teachersâ effort of BK helps adaptation for special necessity of participant to learn, 2) The teachersâ effort of BK helps adaptation for special necessity of participant with friends. The kinds of this research is Descriptive Research that give purpose to describe real condition. The subject of the research is special necessity of participant amount 15 person. The data collection uses questionaires. Meanwhile, the data analysis uses percentage formula. The result of this research expresses that 1) The teachersâ effort of BK helps adaptation for special necessity of participant in learning process 60,00% in category good enough, 2) The teachersâ effort of BK helps adaptation for special necessity of participant with friends 46,67% in category least good.Â